Satellite view of quasi‐equilibrium states in tropical convection and precipitation microphysics. Issue 6 (27th March 2015) - Matsui, Toshi; Tao, Wei‐Kuo; Munchak, S. Joseph; Grecu, Mircea; Huffman, George J.
Abstract: This study shows the time series of statistical composites of precipitation‐microphysics signals derived from long‐term Tropical Rainfall Measuring Mission (TRMM) satellite observations aggregated over the entire tropical domain (37°N–37°S). The result shows the nearly time‐invariant monthly signal statistics throughout this time, confirming convection quasi‐equilibrium (CQE) states. Merged precipitation data, with much better temporal and spatial coverage, provide evidence that the equilibrium state occurs on a daily scale. These results further indicate the presence of precipitation microphysics quasi‐equilibrium (MQE) within the CQE environment. A simple analytic microphysics framework illustrates the equilibrium precipitation size distribution, as compared with the TRMM radar‐based as well as preliminary Global Precipitation Measurement combined retrievals. The MQE readily explains the near‐constant tropical precipitation rate, which is roughly balanced with atmospheric radiative cooling rate at the entire tropical scale. Further investigation is required through theoretical, observational, and numerical manners to support the MQE hypothesis. Key Points: TRMM satellite precipitation signal statistics Convective quasi‐equilibrium Microphysics quasi‐equilibrium hypothesis with TRMM and GPM data